2019
DOI: 10.1590/1516-4446-2018-0126
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of the Mandarin Chinese version of the Yale-Brown Obsessive-Compulsive Scale – Second Edition

Abstract: Objective:To examine the psychometric properties of the Chinese version of the Yale-Brown Obsessive Compulsive Scale – Second Edition (Y-BOCS-II).Method:A total of 86 adults with a primary diagnosis of obsessive-compulsive disorder (OCD), ranging in age from 15 to 78 years, participated in the study. Participants were administered the Y-BOCS-II by a trained clinician who also rated overall illness severity on two additional measures. Patients completed the Obsessive Compulsive Inventory-Revised and Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Previous studies have shown that YBOCS-II has high internal consistency, short-term stability, and good interrater reliability (Storch et al, 2010;. The Chinese version has demonstrated good psychometric properties in Chinesespeaking samples (Zhang et al, 2019). The Y-BOCS-II demonstrated excellent internal consistency in the current sample, α = .90.…”
Section: Methodsmentioning
confidence: 62%
“…Previous studies have shown that YBOCS-II has high internal consistency, short-term stability, and good interrater reliability (Storch et al, 2010;. The Chinese version has demonstrated good psychometric properties in Chinesespeaking samples (Zhang et al, 2019). The Y-BOCS-II demonstrated excellent internal consistency in the current sample, α = .90.…”
Section: Methodsmentioning
confidence: 62%
“…The Y-BOCS-II was revised from its predecessor in several ways, with the goal of incorporating advances in the understanding of OCD phenomenology by increasing sensitivity to changes in symptom severity, systematically integrating avoidance variables in ratings, and improving the psychometric properties of the scale, while maintaining consistency with the Y-BOCS where possible. Indeed, investigations into the psychometrics of the Y-BOCS-II have demonstrated strong internal consistency, sensitivity, reliability, and validity, and a more stable factor structure 10,18–23. Primary updates in the Y-BOCS-II are highlighted below to demonstrate the significant role they play in assessing scenarios such as those presented in this article.…”
Section: Differences Between the Y-bocs And Y-bocs-iimentioning
confidence: 97%
“…The improvements in both his obsessions and compulsions were maintained over the course of the entire follow-up period. At 12-month follow-up, the patient's overall level of OCD symptoms, as measured by using the total score on the Yale-Brown Obsessive-Compulsive Scale (YBOCS-II) (10), was reduced by about 35% as compared to his total score obtained at baseline ( Table 3). After HB DBS onset, the patient also reported improvements in depression, anxiety, and healthrelated quality of life at 3-month follow-up, which were sustained until 12-month follow-up ( Table 3).…”
Section: Case Presentationmentioning
confidence: 98%